Report of the Summer Party of the 11th Japanese Antarctic Research Expedition in 1969-1970 (Reports of the Japanese Antarctic Research Expedition) - Sadao KAWAGUCHI (National Institute of Polar Research, 1972)
Forty members of the 11th Japanese Antarctic Research Expedition left Tokyo on November 25, 1969, aboard the icebreaker FUJI under the command of Captain Hideo ISOBE. The expedition was led by Dr. Tatsuro MATSUDA, also leading the wintering party consisting of 30 men and the author, as deputy-leader, led the summer party of 10 men. At Fremantle, Western Australia, an american exchange scientist, Mr. Herman R. FRIIS and an australian exchange scientist Dr. Garth A. MORGAN got on board the FUJI. The FUJI carried about 560 tons of cargo, including a single-engine monoplane Lockheed LASA-60, and was equipped with two Sikorsky S61-A helicopters and one Bell 47G 2A helicopter. On December 17, the FUJI left Fremantle for Syowa Station and reached the edge of fast ice at 68°36'S, 38°27.5'E, about 35 nautical miles northeast of the Station. On January 2, 1970, from there three flights of helicopters to Syowa Station were made to send on advance party and cargo. On January 5, the FUJI anchored within 1200 meters east of the Station. Unloading of 560 tons cargo was finished on the 20th, of which about 300 tons of materials were transported by two Sikorsky helicopters. Fuel of 180 tons for diesel generators was transported by a pipeline from the ship to the tanks at the Station. Oversnow vehicles and the remaining heavy items were transported over sea ice. Construction of two storages, a vault for installing seismographs and the rocket launching facilities was completed at the end of January. From the end of January to the middle of February several field parties were sent by helicopters to the exposed rock areas of the southern part of Soya Coast for the studies of geology, geomorphology, biology, limnology, glaciology, geodesy and geomagnetism. Aerophotogrammetic surveys were made along the west coast of Lutzow-Holm Bay and Yamato Mountains. A small island was newly discovered at 69°20'S, 37°35.6'E, and a preliminary survey was performed. The two rocket launching experiments of sounding rocket S-160JA (length 3890mm, ...